2013
DOI: 10.1007/s00268-013-2375-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Preoperative Evaluation of the Right Gastroepiploic Artery Graft to the Coronary Artery in Patients Undergoing Abdominal Surgery

Abstract: It is important to determine whether an RGEA graft is present when repeat laparotomy is required after CABG. In cases where an RGEA graft is present, it is essential to evaluate the patency and location of the graft since this will be crucial for planning the reoperation strategy. Preoperative recognition and evaluation of the RGEA graft can help avoid graft injury, even if the graft cannot be detected intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Furthermore, indication should be screened carefully before operation, which is isolated RCA lesion with no gastric ulcer, tumor or other lesions in the stomach and no stenosis in the abdominal aorta and abdominal cavity. Finally, the patient will have a risk of injury to the RGEA when upper abdominal surgery, such as gastric and liver are required in the future 7 ; if surgery for the treatment of stomach cancer is conducted, the removal of infrapyloric lymph nodes will be affected 8 . When these surgeries are required by the patient, the cooperation plan should be formulated by cardiologist, surgeon, anesthesiologist, and operator together to ensure the safety of the patient.…”
Section: Commentsmentioning
confidence: 99%
“…Furthermore, indication should be screened carefully before operation, which is isolated RCA lesion with no gastric ulcer, tumor or other lesions in the stomach and no stenosis in the abdominal aorta and abdominal cavity. Finally, the patient will have a risk of injury to the RGEA when upper abdominal surgery, such as gastric and liver are required in the future 7 ; if surgery for the treatment of stomach cancer is conducted, the removal of infrapyloric lymph nodes will be affected 8 . When these surgeries are required by the patient, the cooperation plan should be formulated by cardiologist, surgeon, anesthesiologist, and operator together to ensure the safety of the patient.…”
Section: Commentsmentioning
confidence: 99%
“…2,60) In 1984, Pym et al were the first to report its use for revascularization of the posterior marginal artery and RCA. 2,61,62) Due to the satisfactory results, this vessel is still considered an option for CABG. 62) The RGEA is considered the third option for CABG.…”
Section: Coronary Arteriesmentioning
confidence: 99%
“…5) One concern is the potential damage of the graft or spasm during abdominal surgery. 62) The main mechanism of graft failure is a reduction in intraluminal diameter or occlusion when used for revascularized arteries with low-grade stenosis. 5) Results of morphological studies of RGEA are shown in Table 5.…”
Section: Coronary Arteriesmentioning
confidence: 99%